Neighbourhood branding and the right to the city. (April 2018) - Masuda, Jeffrey R.; Bookman, Sonia
In this article we seek to encourage geographers to consider the discursive dimensions of urbanization as a locus for activist inquiry into the right to the city. Drawing from literatures on urban branding and critical toponymy, we implicate the entrepreneurial phenomenon of neighbourhood branding as a primary enabler of urban gentrification and dispossession. Placing the discursive elision of local history, identity, and aspirations into dialectical relation to material infringements upon inhabitants' collective rights, we suggest how both branding and activist counter-branding tactics may be fruitful sites for future empirical research on the right to the city.